Pengaruh Fashion Influencer TikTok Terhadap Minat Beli Produk Fashion Wanita Pada Kalangan Remaja - Dianti Dita Putri; NURINA DWI; Novia Indah Lestari (Jurnal Manajemen, 2025)
The emergence of fashion influencers is considered a key factor in contemporary digital marketing trends. This study examines the influence of TikTok fashion influencer Nazwa Adinda on the purchasing interest in women's fashion among teenagers in the Pandeglang District. The research utilizes a quantitative approach, which is conducted through a survey using a questionnaire distributed by Google Forms. The population consists of 21,947 individuals and includes 100 samples, selected using purposive sampling based on the Slovin calculation. This research is grounded in the AIDDA theoretical framework. The results indicate a significant influence of TikTok fashion influencer Nazwa Adinda on the purchasing interest in women's fashion among teenagers in the Pandeglang District, accounting for 63%, while the remaining 37% is influenced by other factors not examined in this study. Keywords: Fashion Influencer, TikTok, AIDDA, Purchase Intention.